(untitled) (Veterinary Science, 2017)
Acaena myriophylla (cadillo) is a rosacea family plant that naturally grows in the pampas area. The Acaena myriophylla extract action over cellular and tissue components on skin wounds in white mice was analyzed. Skin wounds in mice were treated topically with diluted extracts of Acaena myriophylla for 10 days and samples were taken every day for histological analysis. In order to compare the evolution of the wounds the same procedure was applied to a non-treated group of animals. (Control group) Mice from the treated group showed an important local edema and significant delay in the healing wound process evidenced by an increase in neutrophil and fibroblast remain in the injured tissue, (P0,05) as well as in the collagen fiber arrangement in relation to the control group. The statistic test showed significant differences (P0.01) in the number of neutrophil and fibroblast between the treated and untreated mice.